Membangun Partisipasi Siswa Dalam Pemanfaatan Media Promosi Kesehatan Online Perilakuhidupsehat.Org Di SMK Pariwisata Sila Chandra Batubulan, Kecamatan Sukawati Kabupaten Gianyar Tahun 2019 - GA Dewi Kusumayanti; I Putu Suiraoka (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
The opportunity to use the internet as a health promotion strategy is expected to improve the degree of public health. This technology is able to facilitate the delivery of information more closely, reaching healthy but irregular individuals in contact with health services. The purpose of this community service activity is to find out changes in knowledge about healthy living behaviors and participation in the use of online health promotion media "behavior livesehat.org". The target in this community service activity is students at the Sila Chandra Batubulan Tourism Vocational School, Sukawati District, Gianyar Regency. These community service activities are carried out using direct and indirect socialization methods. Evaluation of the process is done by conducting interviews with community service goals, monitoring the level of attendance of community service participants and activeness. In this socialization activity students listened intently to the material presented. The results of the pre-test target show the lowest value of 20 and the highest value of 80 with an average of 52.14 + 15.71. While the post-test results show the lowest value of 50 and the highest of 100 with an average of 70.71 + 10.51. There was a significant increase in knowledge based on paired t test results (p 0.05). Keywords: Online Media, Student, School Health Education Program